Understanding Latin American Cooperation on Antarctic Issues - Lorenzo, Cristian A.
This concluding chapter examines Latin American cooperation on Antarctic issues. In doing so, it adressess the current status quo and its challenges, offers a definition for the Latin American cooperacion, analyzes the underlying factors of cooperative efforts, and the role of geopolitics. Fil: Lorenzo, Cristian A. Universidad Nacional de Tierra del Fuego; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina